Nasolabial changes after two different approaches for surgically assisted rapid maxillary expansion - Alves, N.; Oliveira, T. F.M. [UNESP]; Pereira-Filho, V. A. [UNESP]; Gonçales, E. S.; Gabrielli, M. A.C. [UNESP]; Passeri, L. A. (Elsevier, 2017)
This retrospective study evaluated the nasolabial changes in patients who underwent surgically assisted rapid maxillary expansion (SARME) using two different approaches. Nineteen patients were included in the study, divided into two groups according to the kind of surgical approach performed: group 1 (n = 9), SARME performed through the standard Le Fort I circumvestibular approach followed by the alar base cinch, and group 2 (n = 10), SARME performed through a subtotal vestibular approach associated to a V-shaped incision at the maxillary midline in the labial frenulum region, without alar base cinch. Measurements of width, length, and nasal projection as well as upper lip length were taken from cone beam tomographic images obtained before surgery (T1) and 6 months postoperatively (T2). Both groups presented an increase in the alar base width postoperatively (P < 0.05). The approach used in group 2 resulted in smaller changes in the alar base width as measured at the superior alar curvature (P < 0.05). Nasal length and projection and upper lip length were not altered by SARME. The type of surgical approach influenced nasolabial changes, but did not eliminate increase in width of the alar base.
Keywords: cone beam computed tomography; Le Fort osteotomy; palatal expansion technique